The factor structure of the environmental attitude scale in a community-based study in Lagos, Nigeria (2019)
Environmental Attitude (EA) has been understood to be a complex multidimensional construct with minimal empirical evidence in developing countries. In the present study, psychometric properties of an EA scale was empirically assessed using data from a community based study conducted in Nigeria. Different measures of EA were aggregated into a single EA scale and administered to 1,858 individuals. Mean (Standard deviation) and proportions were used to describe the distribution of continuous and discrete data respectively. Reliability of the scale was assessed using Cronbach's alpha. Varying hypothetical models of the EA were assessed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Data were analyzed using IBM SPSS version 20 and AMOS version 21 at 5% significant level. Overall mean score and alpha coefficient for the combined EA measure was 381.7 (49.0) and 0.928 respectively. A 3-factor structure accounting for 36% cumulative variance in the scale item was extracted in an EFA. A nonorthogonal 3-factor model was a significant improvement over the original none-correlated 5-factor model [÷2 (1344) =29216.33, P<0.001; CAIC=9816.870]. The conceptualization of the EA as a non-orthogonal 3-factor structure provides a better fit to the present data. The 3-factor structure is advised in Nigeria and similar settings.